PENERAPAN ACTION CONTROL DAN RESULT CONTROL UNTUK MENINGKATKAN KINERJA KARYAWAN PRODUKSI PADA PT.GTP DI SURABAYA - Monica Selviana Djasmin (CALYPTRA, 2019)
Abstract Human resources is one of the most important factors in the implementation of control in order to achieve company goals. Competition in the increasingly growing business world requires companies to be able to produce human resources that have the expertise, excellence and quality. The success of a company is strongly influenced by the performance of existing human resources and required a good management control system and appropriate to be able to produce and improve employee performance so that corporate goals can be achieved. Therefore, in this research will be conducted research on management control system by applying Action control and Result control at PT. GTP that aims to improve employee performance and help PT. GTP in overcoming the problems in order to survive in existing business competition. The purpose of this research is explanatory research that explains about the implementation of Action control and Result control to improve employee performance at PT. GTP. The benefit of this research is applied research. Methods of data collection were obtained through interviews, observation and document analysis. This research focuses on the implementation of formal management control system in the form of Action control and Result control on employee performance. And the results of this study will provide recommendations for PT. GTP to be able to improve the existing control at the company so as to improve employee performance. Keywords: Management Control System: Employee Performance: Action control: Result control